2020
DOI: 10.1101/2020.04.21.20073536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-level modeling of early COVID-19 epidemic dynamics in French regions and estimation of the lockdown impact on infection rate

Abstract: We propose a population approach to model the beginning of the French COVID-19 epidemic at the regional level. We rely on an extended Susceptible-Exposed-Infectious-Recovered (SEIR) mechanistic model, a simplified representation of the average epidemic process. Combining several French public datasets on the early dynamics of the epidemic, we estimate region-specific key parameters conditionally on this mechanistic model through Stochastic Approximation Expectation Maximization (SAEM) optimization using Monoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 49 publications
4
49
0
Order By: Relevance
“…Some of these problems can be avoided by explicit use of mathematical models that take into account the prolonged clinical progression of COVID-19 (e.g. [ 12 , 87 ]), which is the first order cause of these delays. However, our results show that transmission network structure also plays an important role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these problems can be avoided by explicit use of mathematical models that take into account the prolonged clinical progression of COVID-19 (e.g. [ 12 , 87 ]), which is the first order cause of these delays. However, our results show that transmission network structure also plays an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time and retrospective analyses of the growth rate of cases and deaths have suggested that in some settings the epidemic eventually slowed after the implementation of strong social distancing measures (e.g. in Wuhan and other Chinese cities [ 8 , 9 ], in Hong Kong [ 10 ], across European countries [ 11 ], French regions [ 12 ], or some US states [ 13 , 14 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The degree distribution in this layer was obtained from the school contact survey data [13], which estimated that the school-going population in the United States, on average, had nSCHOOL ∼ 7.3 ± 1.8 school-related contacts daily. The variance was obtained by the variance in the mean across the school-aged (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) age groups. Individuals were assigned degrees randomly from a binomial distribution with this mean and standard deviation.…”
Section: Five-layer Network Structurementioning
confidence: 99%
“… Berger, Herkenhoff, and Mongey (2020) and Roques, Klein, Papaix, Sar, and Soubeyrand (2020) ). In Prague et al. (2020) , the lockdown effect is estimated using stochastic approximation, expectation maximization and an estimation of basic reproductive numbers.…”
Section: Introductionmentioning
confidence: 99%